(3GdfLjHjGJs - (3GdfLjH GdSeQbfOj , eMeO Hf Ydj Hf YeQ GdSeQbfOj, fLjH GdOjf CHh MGeO,J (B619 (3g` s ((3Hgef Hf Ydi GdcGRQhfi s)
(3ChdgG (B:s
(3GdMeO ddg Ydi fYeGFg GdSGHbI , hGjGOjg GddGMbI Efi bO LeYJ dCLdi ai gPg GdeLdOI eG cGfJ MGLJi Edjg GVWQGQGjI YfO eTGgOI GdeQV heYGdLJge ,dJchf OGFekG Hjf jOi CfXQ ajgG hCSJZfi HgG Yf GdfXQ ai cJH TJi s
(3BNQgG (B:s
(3YV GdCQHYI hGdCQHYjf hYdGLg hQHeG cai ajg GSJYeGd GdedM hGdNd Ydi ehVY GdYVI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3fSNI KGfjIs
(3hgj JTJed Ydi SJI CbSGes
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B280 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B31s
Keywords: (3GdWHs